Special channels in music education, to ensure quality and encourage «talents»? - Grivet Bonzon, Catherine; Mili, Isabelle; Schumacher, Jérôme (Swiss Journal of Educational Research, 2018)
The constitutional article 67A, adopted by the people on September 23, 2012, lays out that: «Within the limits of their respective competences, the Confederation and the cantons commit themselves promoting at the school a musical teaching of quality». The object of this article is to analyze starting from two cases of Musical academies:– The speech on quality in itself,– The nature of the devices planned for the formation of a minority of pupils «with high potential».It is starting from the observation of the regulations (Sensevy & Mercier, 2007) and multiple interactions resulting from the various courses suggested in these courses reinforced that the study will analyze the processes leading to a specific musical performativity, even with a particular quality of teaching.